The New Zealand Government's Efforts in Social Recognition of Motorcycle Gangs as a Social Community in Order to Maintain National Security - Dian Anggraini; Arifuddin Uksan; Kusuma Kusuma; Pujo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
New Zealand faces challenges related to motorcycle gang activities that can threaten national security. In addressing this issue, the New Zealand government has made efforts to recognize motorcycle gangs as social communities to uphold national security. The method used in this research is qualitative research, and new findings regarding the research object will be supported by data collection techniques, such as structured interviews and group discussion with the Director of The Toda Peace Institute - Professor Kevin Paul Clements. This approach aims to change the negative perception of motorcycle gangs and involve them in more positive activities. In the government's efforts of social recognition towards motorcycle gangs as social communities, a softer policy approach is adopted. In this context, the government acknowledges the existence of motorcycle gangs as communities within society. This step aims to strengthen the social identity of motorcycle gangs and provide recognition to the community. The presence of motorcycle gangs in New Zealand poses significant security challenges. By enhancing their connection with the wider community, it can help maintain national security by engaging this community in positive and constructive endeavors. With this research, it is also hoped to contribute insights and recommendations to the Indonesian government on appropriate and suitable approaches to tackle the issue of motorbike gangs in Indonesia.